Y-Balance Test Results and Therapeutic Intervention in a Group of Recreational Long-Distance Runners with Femoroacetabular Impingement - Robert Walaszek; Katarzyna Burdacka; Wiesław Chwała; Marcin Burdacki; Paweł Kurowski (Rehabilitacja Medyczna)
Introduction: Running, apart from walking, is one of the most natural manners of movement. Disturbances in the statics and dynamics of the pelvic girdle can interfere with running rhythm and directly affect its technique.Objectives: The aim of the study was to assess the impact of a therapeutic intervention on changes in dynamic balance in individuals with femoroacetabular impingement (FAI), recreationally practising long-distance running.Material and methods: The study involves 44 men, aged 30 to 50, who practise recreational long-distance running. Two runs of tests were conducted at the Laboratory of Biokinetics, University of Physical Education in Kraków. The first measurements were carried out in January 2020, and the second ones – after a six-month therapeutic intervention, in July of 2020. The therapeutic programme consisted of mobilising the hip joint in all physiological planes over a painless and safe range of motion. Balance measurements in dynamic conditions were performed using the Y-Balance test (YBT).Results: The second examination showed a significant increase in the mean YBT1 value for the affected limb in the experimental group, the mean YBT2 value for both limbs in the experimental group and the right limb in the control group, the mean YBT3 value for both limbs in the experimental group, and the mean YBTT value for both limbs in the experimental group and for the right limb in the control group.Conclusions: Both before and after the therapeutic intervention, certain statistically significant differences were found in dynamic balance between runners with FAI and n-FAI. After the intervention, the values of the analysed variables in runners with FAI were more similar to those observed in the control group. The results of the conducted research enable the practical use of the proposed original intervention, which is a comprehensive six-month rehabilitation programme in the conservative treatment of physically active people with FAI.